2022
DOI: 10.1002/hrm.22159
|View full text |Cite
|
Sign up to set email alerts
|

Gender diversity advantage at middle management: Implications for high performance work system improvement and organizational performance

Abstract: Research on women in leadership positions has largely focused on the board or top management team (TMT) leadership level, showing that increased female representation at these levels can benefit organizational performance. However, the strategic implications of female representation at middle management have been largely neglected. The current study addresses this issue in relation to High Performance Work System (HPWS) improvement and organizational performance (profitability). By analyzing the multi‐wave (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 155 publications
0
1
0
Order By: Relevance
“…Human resource management has long been interested in increasing women's managerial representation to address gender equity issues and enhance business performance (Ali et al, 2014; Galbreath, 2018; Joo et al, 2023; Kirsch, 2018; Wu et al, 2022). Our study speaks to a growing awareness of how workplace diversity shapes subsequent managerial appointments (Biswas et al, 2023; Gould et al, 2018a; Kulik et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Human resource management has long been interested in increasing women's managerial representation to address gender equity issues and enhance business performance (Ali et al, 2014; Galbreath, 2018; Joo et al, 2023; Kirsch, 2018; Wu et al, 2022). Our study speaks to a growing awareness of how workplace diversity shapes subsequent managerial appointments (Biswas et al, 2023; Gould et al, 2018a; Kulik et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The structural equation model includes two basic models: the measurement model and the structural model. The measurement model is a linear function of the observed variables, and the structural model is the relationship between the latent variable A of psychological capital as an exogenous factor and the latent variable B of Corporate Performance as an outcome (Joo et al, 2022). Based on the common formula in structural equation modeling, the regression equation in the measurement model is expressed as:…”
Section: Modeling Of Structural Equation Assumptionsmentioning
confidence: 99%
“…Previous studies have utilized outcomes such as employee engagement [45], job performance [5][6][7][8][9], organizational citizenship behavior [46,47], and job satisfaction [37,48] at the individual level as dependent variables for HPWSs. The majority of the previous research on individual-level HPWS perception has demonstrated a positive relationship between HPWS perception and organizational performance [5,8,49].…”
Section: The Relationship Between the Perception Of A High-performanc...mentioning
confidence: 99%
“…To effectively manage employees, both academia and industry have long focused on highperformance work systems, which refer to a specific set of HR strategies, work structures, and processes that maximize employee knowledge, skill, dedication, and adaptability [5], as innovative human resource management systems. Numerous previous studies have shown the positive effects of high-performance work systems on organizational performance [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%